Plec mozgu : o prawdziwej roznicy miedzy mezczyzna a kobieta - Moir, Anne.; Jessel, David (Warszawa : Panstwowy Instytut Wydawniczy, 1999)
Polish translation of "Brain Sex". The authors propose that physiological evidence suports the notion that men and women are not made the same, that there are genetic predispositions to certain kinds of work, conduct and attitudes which vary from men to women.
Includes bibliographical references (p. 271-[297]).
Keywords: Sex differences; Sex differences (Psychology); Brain -- Sex differences